Response Surface Methodology Based Development and Quantification of Celecoxib and Amlodipine Using RP-HPLC.: Pharmaceutical Science-Pharmaseutical Analysis - B. Shah, Darshil; H. Patel, Bhavesh; S. Shah, Jignesh (International Journal of Life Science and Pharma Research, 2022)
A novel RP-HPLC method for estimation of Amlodipine Besylate and Celecoxib using an experimental design approach employing response surface technique was developed and validated using a C18 column and its application in marketed formulation. A multivariate optimization of experimental conditions was carried out using experimental design employing organic content in the mobile phase, pH, and flow rate of the mobile phase as three independent variables. The aim of the study was to apply response surface methodology and to study the effect of the independent variables on separation and estimation of both drugs by RP-HPLC method using faced central composite (FCC) experimental design which is novel in this area of research. Optimization of retention time of the last eluting peak and peak symmetry was performed using Derringer’s desirability function in which potassium dihydrogen phosphate buffer with pH 4. 45, 25 mM, 0.5% Triethylamine and acetonitrile in an isocratic proportion of 70:30% v/v and 1.2 ml/min flow rate was found to be the predicted optimum condition. DoE approach based RP-HPLC method development using response surface methodology led to efficient separation with a lower retention time of eluted peaks below 7 min indicating novelty of research. A linear response was observed over the concentration range of 40-240 μg/mL for Celecoxib and 1-6 μg/ mL for Amlodipine Besylate. Limit of detection (LOD) and limit of quantitation (LOQ) for Celecoxib were found to be 0.02 μg/mL and 0.08μg/mL, and for Amlodipine Besylate were 0.0053 μg/mL and 0.0162 μg/mL, respectively. The method was successfully validated in accordance with ICH guideline acceptance criteria for linearity, accuracy, precision, specificity, robustness.